Collagen hydrogel protects intestinal epithelial cells from indomethacin-induced damage: results of an in vitro experiment - Pavel A. Markov; Andrey S. Sokolov; Irina A. Artemyeva; Ilmira R. Gilmutdinova; Anatoliy D. Fesyun; Petr S. Eremin (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2024)
INTRODUCTION. Indomethacin is a derivative of indoleacetic acid and has anti-inflammatory, analgesic and antipyretic effects. However, the results of numerous studies show that indomethacin, like many other nonsteroidal anti-inflammatory drugs (NSAIDs), have an inhibitory effect on the viability and functional activity of enterocytes. In this regard, the search for new ways to reduce the severity of side effects from the use of NSAIDs remains relevant. One of these approaches may be to enrich patients' diets with non-drug biologically active compounds, including proteins. However, the effect of dietary proteins and biologically active peptides on NSAID-induced damage to the wall of the small intestine and stomach has not been sufficiently studied. AIM. To evaluate the ability of a collagen-containing dietary supplement to protect human duodenal epithelial cells (HuTu-80 line) from indomethacin-induced damage. MATERIALS AND METHODS. The composite collagen-containing hydrogel was provided by «FIRST ALIVE COLLAGEN» LLC (Russia) and is a registered dietary supplement. The work used a commercial culture of human skin fibroblast cells and human duodenal epithelial cells (line HuTu-80). The viability of intestinal cells and fibroblasts was assessed using light and fluorescence microscopy and flow cytometry methods. RESULTS AND DISCUSSION. It has been established that indomethacin inhibits cell growth, causes apoptosis and death of enterocytes, and also leads to the accumulation of cells in the S-phase, which indicates a disruption in the regulation of the cell cycle. It was revealed that collagen hydrogel prevents cell death caused by indomethacin and reduces the number of apoptotic cells in the population. The protective effect of collagen hydrogel is characterized by normalization of the cell cycle of enterocytes and restoration of their growth and proliferative activity. CONCLUSION. Thus, collagen hydrogel, in vitro, is able to reduce the pathogenic effect of indomethacin on human intestinal epithelial cells. The protective effect of collagen hydrogel is characterized by maintaining viability, inhibiting apoptotic processes, and maintaining cell cycle stability. The results obtained indicate the prospects of using a dietary supplement based on a composite collagen hydrogel as a prophylactic agent to reduce the risk of NSAID-associated gastrointestinal diseases. However, to confirm the therapeutic effectiveness of the dietary supplement, further research is necessary, both using experimental animal modeling of NSAID-associated diseases of the human gastrointestinal tract, and clinical studies.